LA ATENCIÓN AL RIESGO, UN IMPERATIVO DE LA ESCUELA CUBANA - Fuentes Abreu , Norma; Montero Machado , Isabel; Nieves Achón, Susana (Varela Journal, 2008)
An exigence of the cuban school is to offer the risk attention, that’s why this work proposes to accomplish its study, establishing a relation among the risks, that one way or another emerge and are shown at external conditions of the social situation of development out of every little boy or girl and risks to a level micro, caused for various factors like the biological environmental, economic, psychological and socials, and educational, among others.